ADMINISTRATION OF ACCESS TO CAPITAL IN POST-REDISTRIBUTION OF LAND IN AN ISLAMIC VIEW - Rahmat Ramadhani; Ida Hanifah; Farid Wajdi (Proceeding International Seminar of Islamic Studies, 2023)
Land issues are not only related to land disputes, conflicts and cases, but are also related to gaps in land tenure and land conversion which are considered to be inhibiting factors in achieving land as the greatest source of people's prosperity. Arranging access to capital after land redistribution within the framework of agrarian reform is one of the government's steps to address the issue of land management in Indonesia which will be studied from an Islamic perspective. This study uses a normative legal research method using secondary data which is analyzed through content analysis with a statua approach. The results showed that the aspect of post-land redistribution capital has a correlation with economic activity in the view of Islam as a whole, which aims to: meet one's basic needs, meet family needs, meet long-term needs, provide for the needs of abandoned families, provide social assistance and donations in the way of Allah SWT. The fundamental value of Islamic teachings regarding the post-land redistribution capital aspect as stated above is in line with the basic nature of agrarian reform activities in Indonesia which are characterized by democracy, social justice for land. Arrangement of access to capital after land redistribution is a form of continuity and equality between asset arrangement in the form of equal distribution of land ownership and access arrangement in the form of community empowerment to access capital based on land rights so as to realize community welfare.